PENGARUH PEMBERIAN BUTIR LEUSIT DAN KONSENTRASI HNO3 TERHADAP KETERSEDIAAN K ENTISOLS BENGAWAN SOLO DENGAN INDIKATOR TANAMAN KACANG TANAH (Arachis hypogaea. L) - Abdurrakhman WKA; Sri Hartati; Hery Widijanto (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2010)
Title : The Effect of Leucite Grain and Nitric Acid Concentration on Potassium Availability of Bengawan Solo Entisols with Peanuts as Plant Indicator (Arachis hypogaea.  L). Research in the Glass House of Agriculture Faculty of Sebelas Maret University have been made to study the effect of Leucite grain and nitric acid concentration against availability of potassium from Bengawan Solo Entisols made in April – September 2006. This research is a causal relationship functional research; the approach is done with variables factorial experiment using Complete Random Design (CRD) with 2 factors and 3 times repeated. First factor is adding the Leucite grain (L) consist of 4 stage, that is L0 (without Leucite), L1 (using 5 mesh of Leucite grain), L2 (using 30 mesh of Leucite grain) and L3 (using 80 mesh size of Leucite grain). Second is adding acid concentration of nitrate (M), consists of 4 stage that is M0 (without nitric acid), M1 (adding 0.1M of nitric acid), M2 (adding 0.2M of nitric acid), and M3 (adding 0,3M of nitric acid). The first shaken with second factor for 24 hours before applied to soil. Analysis of data is using Analysis of Variance and Duncan’s Multiple Range Test. Results of research shows the high K dissolved value on the acid concentration of nitrate with 10-1M after the first 24 hours shaking between the two factors, with soluble K value 172.52 cmol/kg of L1M1 addition, 120.48 cmol/kg of L2M1 addition, and 188.13 cmol/kg of L3M1 addition. Adding Leucite grain and nitric acid concentrations have lower soil available K value at the time of incubation with a value that is lower than 0.30 cmol / kg (L0M0 – control of treatment). In stage of maximum vegetative, the additions of two factors have to increase the value of average soil available K was 0.30 cmol/kg on the L3M2. K absorption by plants has the highest average value of 0.73 mg/ kg on L3M3 Keyword: Leucite, Nitrite acid, potassium availability, potassium absorption, weathering